2011
DOI: 10.1103/physreva.84.033420
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton ionization of H2+in xuv laser pulses

Abstract: We consider the ionization of the hydrogen molecular ion after one-, two-, and three-photon absorption over a large range of photon energies between 9 and 40 eV in the fixed-nuclei approximation. The temporal development of the system is obtained in a fully ab initio time-dependent grid-based approach in prolate spheroidal coordinates. The alignment dependence of the one-photon ionization amplitude is highlighted in the framework of time-dependent perturbation theory. For one-photon ionization as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
59
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 36 publications
5
59
3
Order By: Relevance
“…In a recent work [25], it was found that the corresponding process in H − is characterized by a strong backward-forward asymmetry in the sense that if one electron is emitted perpendicular to the (linear) laser polarization direction then the other electron is emitted most preferably in the opposite direction, forming three characteristic lobes in the angular distribution. Similar features have also been observed theoretically in H 2 [26][27][28].…”
supporting
confidence: 73%
See 2 more Smart Citations
“…In a recent work [25], it was found that the corresponding process in H − is characterized by a strong backward-forward asymmetry in the sense that if one electron is emitted perpendicular to the (linear) laser polarization direction then the other electron is emitted most preferably in the opposite direction, forming three characteristic lobes in the angular distribution. Similar features have also been observed theoretically in H 2 [26][27][28].…”
supporting
confidence: 73%
“…In a recent work [25], it was found that the corresponding process in H − is characterized by a strong backward-forward asymmetry in the sense that if one electron is emitted perpendicular to the (linear) laser polarization direction then the other electron is emitted most preferably in the opposite direction, forming three characteristic lobes in the angular distribution. Similar features have also been observed theoretically in H 2 [26][27][28].Solving the time-dependent Schrödinger equation numerically for helium [14], the conditional angular distribution is obtained for both short (500 and 1000 as) and long (4 fs) linearly polarized laser pulses. We examine the case where one of the electrons is emitted perpendicular to the laser polarization direction, and integrate over the energy of both electrons.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…The study of fundamental breakup processes in nature is important and paves the way for further investigations of the role of correlations in few and multiphoton multiple ionization processes in atoms and molecules. More recently, the four-body breakup of H 2 by two-photon impact has received considerable attention, both in the direct [34][35][36][37] and sequential regime [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Clear discrepancies in the respective triple-differential cross sections were found. Even more recently, Guan et al [36,37] calculated the corresponding cross sections using a fully ab initio, nonperturbative approach, solving the time-dependent Schrödinger equation in prolate spheroidal coordinates for a 10 cycle laser pulse of peak intensity 10 14 W/cm 2 . The cross sections were obtained projecting the final continuum wave function onto a set of uncorrelated two-center Coulomb waves, and the results were found to differ from those reported by both Colgan et al [34] and Morales et al [35].…”
Section: Introductionmentioning
confidence: 99%